2015
DOI: 10.1007/s11468-015-0023-2
|View full text |Cite
|
Sign up to set email alerts
|

A Polarization Filter Based on Photonic Crystal Fiber with Asymmetry Around Gold-Coated Holes

Abstract: We propose a modified design for a photonic crystal fiber (PCF) filter based on surface plasmon resonance(SPR). The air holes are arrayed in rectangular lattices, while the size and the pitches of holes around the gold-coated holes are different. That can separate the x-polarization and y-polarization of second-order surface plasmon polariton (SPP). The resonance strength of the surface plasmon mode and import of structural parameters of the PCF on the filter characteristics are studied through using the finit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…We can see that the amplitude sensitivities are nearly unchanged. As a result, the birefringence intensity can be tailored by adjusting d 2 , which can be used in fiber loop mirrors or polarization filters as described in [16][17][18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We can see that the amplitude sensitivities are nearly unchanged. As a result, the birefringence intensity can be tailored by adjusting d 2 , which can be used in fiber loop mirrors or polarization filters as described in [16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the effective index of the core-guided mode can be tailored by changing the geometrical parameters of the structure, which helps in phase matching of core-guided mode and plasmon mode. PCF can potentially be made highly birefringent as the fabrication process permits the formation of the required microstructure near the fiber core [15], which can be widely used in fiber loop mirrors [16] or polarization filters [17,18]. PCF-based sensor also has a better mechanical stability than ordinary fiber based as it need not strip the fiber jacket and cladding, which destroy the fiber integrity.…”
Section: Introductionmentioning
confidence: 99%
“…An important parameter for the analysis is the confinement loss ( ), defined as where is the wave vector in free space, Im[ ] is the imaginary part of the core-guided mode effective refractive index. Under the phase-matching condition, Im[ ] is considerable enhanced due to the resonant coupling between the core-guided mode and the SPR mode [ 22 ]. Therefore, changes in can be used to monitor the SPR excitation in the structure.…”
Section: Pcf Design and Modelingmentioning
confidence: 99%
“…The cross-section of these SPR-PCFs are usually made by periodic arranges of air holes, some of which are filled or coated with metallic components, surrounding one or more cores (where light is confined). The SPR excitation is thus reached in PCFs through the phase-matching between the core-mode and the surface plasmon mode, i.e., when both modes have the same effective refractive indices [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. In spite of the extensive research efforts on plasmonic PCFs, the narrow frequency range for SPR excitation constitutes a major hurdle for practical applications in, for example, sensors and multiband polarization beam splitters and filters [ 16 , 17 , 30 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed the PWDT characteristic from the SPP resonance of the Au nanowire and the fiber core. There are a number of numerical studies on the polarization characteristics of metal-filled PCF that have been reported recently [8,[15][16][17][18][19][20][21]24,[27][28][29]. On the other hand, Xue et al in 2013 reported a polarization filter of Au-coated PCF and claimed that the resonance loss at 1311 nm wavelength was 508 dB/cm in y-polarization.…”
Section: Introductionmentioning
confidence: 99%